Principles of Management Accounting: A Critique - Musov, Michael (Research Papers, 2023)
This paper gives a critical evaluation of the five main sets of management accounting principles formulated in the accounting literature over the last eighty years. The aim is to problematize management accounting principles as a crucial research area that requires reconsideration and integration of contemporary achievements in science. The main weaknesses of the existing management accounting principles have been identified. These weaknesses are due to the theoretical foundations used or the inductive approach applied. They lead to the uncritical acceptance of the old imperative that, by definition, there is a direct relationship between management accounting information and the organizational value created. The moderating role of the human aspects remains somehow widely underestimated. These aspects make the creation of organizational value a behavioral problem that requires behavioral solutions. A possible behavioral solution is to further develop management accounting principles in the field of behavioral sciences and to work on the development of behavioral principles of management accounting. This general idea concludes the contribution of the paper to the existing accounting literature.